The Effect of Musyarakah Financing on Economic Development in Indonesia (Case Study on Islamic Commercial Banks for the 2018-2022 Period) - Agustina, Ingrid Larasati; Hadi, Dudi Abdul; Dyahrini, Wien (Ekonomis: Journal of Economics and Business, 2024)
This research is motivated by the inequality of economic development in Indonesia through the achievement of the Human Development Index in each province in Indonesia. Then, Islamic Commercial Banks carry out the technical sharing of the results of the musyarakah financing business with net revenue sharing, so that Islamic Commercial Banks tend not to know the working capital rotated by customers experiencing losses or profits. The purpose of this study is to analyze the effect of musyarakah financing on economic development. This study uses an empirical juridical approach with quantitative research types and analytical descriptive research methods. The data used is panel data from Islamic Commercial Banks registered with the Financial Services Authority (OJK) for the 2018-2022 period. The sampling method used in this research is a non-probability sampling technique, while the data processing method is regression analysis using EViews 12. The results of this study indicate that musyarakah financing has an insignificant positive effect on economic development with the Human Development Index as an indicator with a significance level of 0.2113 greater than 0.05. The coefficient of determination with an adjusted R square value of 0.017605 indicates that the influence of musyarakah on economic development is 1.7605%, while the remaining 98.2395% is influenced by other variables outside the study.